Functional characterization of a flavonoid glycosyltransferase gene from withania somnifera (Ashwagandha) - Singh, Somesh; Vishwakarma, Rishi. K.; Kumar, R. J. Santosh; Sonawane, Prashant D.; Ruby; Khan, Bashir Mohammad (Applied Biochemistry and Biotechnology, 2013)
Glycosylation of flavonoids is mediated by family 1 uridine diphosphate (UDP)-dependent glycosyltransferases (UGTs). Until date, there are few reports on functionally characterized flavonoid glycosyltransferases from Withania somnifera. In this study, we cloned the glycosyltransferase gene from W. somnifera (UGT73A16) showing 85-92 % homology with UGTs from other plants. UGT73A16 was expressed as a His(6)-tagged fusion protein in Escherichia coli. Several compounds, including flavonoids, were screened as potential substrates for UGT73A16. HPLC analysis and hypsochromic shift indicated that UGT73A16 transfers a glucose molecule to several different flavonoids. Based on kinetic parameters, UGT73A16 shows more catalytic efficiency towards naringenin. Here, we explored UGT73A16 of W. somnifera as whole cell catalyst in E. coli. We used flavonoids (genistein, apigenin, kaempferol, naringenin, biochanin A, and daidzein) as substrates for this study. More than 95 % of the glucoside products were released into the medium, facilitating their isolation. Glycosylation of substrates occurred on the 7- and 3-hydroxyl group of the aglycone. UGT73A16 also displayed regiospecific glucosyl transfer activity towards 3-hydroxy flavone compound, which is the backbone of all flavonols and also for a chemically synthesized compound, not found naturally. The present study generates essential knowledge and molecular as well as biochemical tools that allow the verification of UGT73A16 in glycosylation.
Keywords: Flavonoid; glycosylation; Glycosyltransferase; Hypsochromic shift; Plant secondary product glycosyltransferase (PSPG); Withania somnifera

Functional characterization of a glucosyltransferase specific to flavonoid 7-O-glucosides from withania somnifera - Kumar, R. J. Santosh; Ruby; Singh, Somesh; Sonawane, Prashant D.; Vishwakarma, R. K.; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Flavonoids are a large class of phenylpropanoid-derived secondary metabolites, which are usually glycosylated by UDP-glycosyltransferases with one or more sugar groups. Here, we report the cloning and biochemical characterization of a flavonoid glycosyltransferase gene from Withania somnifera (WsGT), which is an important medicinal plant used in Ayurvedic formulations. Using PCR primers, designed for a highly conserved region of previously reported glycosyltransferases, we were able to isolate the corresponding fragment of the WsGT gene. Rapid amplification of cDNA ends (RACE) was then employed to isolate full-length cDNA, which had an open reading frame of 1,371 bp that encode for 456 amino acids. Phylogenetic analysis indicated that WsGT was similar to that of family 1 GT-B glycosyltransferase. Biochemical analysis revealed that WsGT interacts with UDP-glucose and was capable of regiospecifically glycosylating flavonoid-7-ols, such as apigenin, naringenin, luteolin, diadzein and genistein. Expression profiling studies showed that WsGT was highly expressed in young and mature leaves of W. somnifera. Furthermore, exposure to salicylic acid enhanced the expression of WsGT in the leaves and heat shock treatment resulted in decreased expression of WsGT after an initial increase. This may suggest the role of WsGT in response to abiotic/biotic stresses.
Keywords: Diadzein; Flavonoids; Glycosyltransferase; Withania somnifera

Molecular cloning, biochemical characterization, and differential expression of an acetyl-CoA C-acetyltransferase gene (AACT) of brahmi (Bacopa monniera) - Vishwakarma, Rishi K.; Ruby; Singh, Somesh; Sonawane, Prashant D.; Srivastava, Sameer; Kumari, Uma; Kumar, R. J. Santosh; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Bacopa monniera (Brahmi) is an important Indian medicinal herb found in wet damp and marshy places. It produces medicinally important compounds known as bacosides along with alkaloids like brahmine and herpestine. Bacosides are triterpenoid saponins and their biosynthesis takes place via the isoprenoid pathway starting with acetyl-CoA. Acetyl-CoA C-acetyltransferase (AACT; EC 2.3.1.9), also known as acetoacetyl-CoA thiolase (Thiolase II), catalyzes the condensation of two acetyl-CoA to form 4-C compound acetoacetyl-CoA. Acetoacetyl-CoA is an important starting molecule for biosynthesis of various metabolites. Here, we report the cDNA cloning and characterization of acetyl-CoA C-acetyltransferase gene from B. monniera. The full-length gene was isolated using a RACE PCR protocol. The cDNA encoding AACT was designated as BmAACT (FJ947159) revealed an ORF of 1,218 bp and 405 amino acids, and shares 80 % similarity with other plant AACTs. Phylogenetic analysis showed that BmAACT is related closely to other dicot plants AACTs. The BmAACT gene was over-expressed in Escherichia coli as a 6X His-tag fusion protein and purified to homogeneity by Ni-NTA and gel filtration chromatography. Activity of recombinant protein was confirmed by thiolytic cleavage of acetoacetyl-CoA in the presence of 5 mM Mg2+, showing K (m) and V (max) of 20.67 mu M and 96.21 mu mol/min, respectively, with high catalytic efficiency (k (cat) = 2.30 x 10(5) min(-1)). Quantitative real-time PCR analysis showed that the expression of BmAACT is tissue-specific, and accumulation of transcripts is greater in roots and petals, followed by sepals, stem, leaf and pedicel.
Keywords: Acetyl-CoA C-acetyltransferase; Bacopa monniera; Isoprenoid pathway; Triterpenoid saponin

Conformational transitions of cinnamoyl CoA reductase 1 from leucaena leucocephala - Sonawane, Prashant D.; Khan, Bashir Mohammad; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2014)
Conformational transitions of cinnamoyl CoA reductase, a key regulatory enzyme in lignin biosynthesis, from Leucaena leucocephala (L1-CCRH1) were studied using fluorescence and circular dichroism spectroscopy. The native protein possesses four trp residues exposed on the surface and 66% of helical structure, undergoes rapid structural transitions at and above 45 C and starts forming aggregates at 55 C. LI-CCRH1 was transformed into acid induced (pH 2.0) molten globule like structure, exhibiting altered secondary structure, diminished tertiary structure and exposed hydrophobic residues. The molten globule like structure was examined for the thermal and chemical stability. The altered secondary structure of Ll -CCRH1 at pH 2.0 was stable up to 90 C. Also, in presence of 0.25 M guanidine hydrochloride (GdnHCI), it got transformed into different structure which was stable in the vicinity of 2 M GdnHCI (as compared to drastic loss of native structure in 2 M GdnHC1) as seen in far UV-CD spectra. The structural transition of LI-CCRH1 at pH 2.0 followed another transition after readjusting the pH to 8.0, forming a structure with hardly any similarity to that of native protein. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aggregation Cinnamoyl CoA reductase; Conformation; Molten globule; Thermostability; Unfolding

GAME9 regulates the biosynthesis of steroidal alkaloids and upstream isoprenoids in the plant mevalonate pathway - Cardenas, Pablo D.; Sonawane, Prashant D.; Pollier, Jacob; Vanden Bossche, Robin; Dewangan, Veena; Weithorn, Efrat; Tal, Lior; Meir, Sagit; Rogachev, Ilana; Malitsky, Sergey; Giri, Ashok P.; Goossens, Alain; et al. (Nature Communications, 2016)
Steroidal glycoalkaloids (SGAs) are cholesterol-derived molecules produced by solanaceous species. They contribute to pathogen defence but are toxic to humans and considered as anti-nutritional compounds. Here we show that GLYCOALKALOID METABOLISM 9 (GAME9), an APETALA2/Ethylene Response Factor, related to regulators of alkaloid production in tobacco and Catharanthus roseus, controls SGA biosynthesis. GAME9 knockdown and overexpression in tomato and potato alters expression of SGAs and upstream mevalonate pathway genes including the cholesterol biosynthesis gene STEROL SIDE CHAIN REDUCTASE 2 (SSR2). Levels of SGAs, C24-alkylsterols and the upstream mevalonate and cholesterol pathways intermediates are modified in these plants. Delta(7)-STEROL-C5(6)-DESATURASE (C5-SD) in the hitherto unresolved cholesterol pathway is a direct target of GAME9. Transactivation and promoter-binding assays show that GAME9 exerts its activity either directly or cooperatively with the SlMYC2 transcription factor as in the case of the C5-SD gene promoter. Our findings provide insight into the regulation of SGA biosynthesis and means for manipulating these metabolites in crops.

Enhanced activity of Withania somnifera family-1 glycosyltransferase (UGT73A16) via mutagenesis - Singh, Somesh; Patel, Krunal A.; Sonawane, Prashant D.; Vishwakarma, Rishi K.; Khan, Bashir M. (World Journal Of Microbiology & Biotechnology, 2018)
This work used an approach of enzyme engineering towards the improved production of baicalin as well as alteration of acceptor and donor substrate preferences in UGT73A16. The 3D model of Withania somnifera family-1 glycosyltransferase (UGT73A16) was constructed based on the known crystal structures of plant UGTs. Structural and functional properties of UGT73A16 were investigated using docking and mutagenesis. The docking studies were performed to understand the key residues involved in substrate recognition. In the molecular model of UGT73A16, substrates binding pockets are located between N- and C-terminal domains. Modeled UGT73A16 was docked with UDP-glucose, UDP-glucuronic acid (UDPGA), kaempferol, isorhamnetin, 3-hydroxy flavones, naringenin, genistein and baicalein. The protein-ligand interactions showed that His 16, Asp 246, Lys 255, Ala 337, Gln 339, Val 340, Asn 358 and Glu 362 amino acid residues may be important for catalytic activity. The kinetic parameters indicated that mutants A337C and Q339A exhibited 2-3 fold and 6-7 fold more catalytic efficiency, respectively than wild type, and shifted the sugar donor specificity from UDP-glucose to UDPGA. The mutant Q379H displayed large loss of activity with UDP-glucose and UDPGA strongly suggested that last amino acid residue of PSPG box is important for glucuronosylation and glucosylation and highly specific to sugar binding sites. The information obtained from docking and mutational studies could be beneficial in future to engineer this biocatalyst for development of better ones.

Pathways to defense metabolites and evading fruit bitterness in genus Solanum evolved through 2-oxoglutarate-dependent dioxygenases - Cardenas, Pablo D.; Sonawane, Prashant D.; Heinig, Uwe; Jozwiak, Adam; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Pliner, Margarita; Unger, Tamar; Wolf, Dalia; Ofner, Itai; Vilaprinyo, Ester; et al. (Nature Communications, 2019)
The genus Solanum comprises three food crops (potato, tomato, and eggplant), which are consumed on daily basis worldwide and also producers of notorious anti-nutritional steroidal glycoalkaloids (SGAs). Hydroxylated SGAs (i.e. leptinines) serve as precursors for leptines that act as defenses against Colorado Potato Beetle (Leptinotarsa decemlineata Say), an important pest of potato worldwide. However, SGA hydroxylating enzymes remain unknown. Here, we discover that 2-OXOGLUTARATE-DEPENDENT-DIOXYGENASE (2-ODD) enzymes catalyze SGA-hydroxylation across various Solanum species. In contrast to cultivated potato, Solanum chacoense, a widespread wild potato species, has evolved a 2-ODD enzyme leading to the formation of leptinines. Furthermore, we find a related 2-ODD in tomato that catalyzes the hydroxylation of the bitter a-tomatine to hydroxytomatine, the first committed step in the chemical shift towards downstream ripening-associated non-bitter SGAs (e.g. esculeoside A). This 2-ODD enzyme prevents bitterness in ripe tomato fruit consumed today which otherwise would remain unpleasant in taste and more toxic.

2-oxoglutarate-dependent dioxygenases drive expansion of steroidal alkaloid structural diversity in the genus Solanum - Sonawane, Prashant D.; Jozawiak, Adam; Barbole, Ranjit; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Gharat, Sachin A.; Ramot, Ofir; Unger, Tamar; Wizler, Guy; Meir, Sagit; Rogachev, Ilana; et al. (New Phytologist, 2022)
Solanum steroidal glycoalkaloids (SGAs) are renowned defence metabolites exhibiting spectacular structural diversity. Genes and enzymes generating the SGA precursor pathway, SGA scaffold and glycosylated forms have been largely identified. Yet, the majority of downstream metabolic steps creating the vast repertoire of SGAs remain untapped. Here, we discovered that members of the 2-OXOGLUTARATE-DEPENDENT DIOXYGENASE (2-ODD) family play a prominent role in SGA metabolism, carrying out three distinct backbone-modifying oxidative steps in addition to the three formerly reported pathway reactions. The GLYCOALKALOID METABOLISM34 (GAME34) enzyme catalyses the conversion of core SGAs to habrochaitosides in wild tomato S. habrochaites. Cultivated tomato plants overexpressing GAME34 ectopically accumulate habrochaitosides. These habrochaitoside enriched plants extracts potently inhibit Puccinia spp. spore germination, a significant Solanaceae crops fungal pathogen. Another 2-ODD enzyme, GAME33, acts as a desaturase (via hydroxylation and E/F ring rearrangement) forming unique, yet unreported SGAs. Conversion of bitter alpha-tomatine to ripe fruit, nonbitter SGAs (e.g. esculeoside A) requires two hydroxylations; while the known GAME31 2-ODD enzyme catalyses hydroxytomatine formation, we find that GAME40 catalyses the penultimate step in the pathway and generates acetoxy-hydroxytomatine towards esculeosides accumulation. Our results highlight the significant contribution of 2-ODD enzymes to the remarkable structural diversity found in plant steroidal specialized metabolism.
Keywords: Solanum; specialized metabolism; steroidal glycoalkaloids (SGAs); structural diversity; Tomato

Steroidal alkaloids defence metabolism and plant growth are modulated by the joint action of gibberellin and jasmonate signalling - Panda, Sayantan; Jozwiak, Adam; Sonawane, Prashant D.; Szymanski, Jedrzej; Kazachkova, Yana; Vainer, Andrii; Kilambi, Himabindu Vasuki; Almekias-Siegl, Efrat; Dikaya, Varvara; Bocobza, Samuel; Shohat, Hagai; Meir, Sagit; et al. (New Phytologist, 2022)
Steroidal glycoalkaloids (SGAs) are protective metabolites constitutively produced by Solanaceae species. Genes and enzymes generating the vast structural diversity of SGAs have been largely identified. Yet, mechanisms of hormone pathways coordinating defence (jasmonate; JA) and growth (gibberellin; GA) controlling SGAs metabolism remain unclear. We used tomato to decipher the hormonal regulation of SGAs metabolism during growth vs defence tradeoff. This was performed by genetic and biochemical characterisation of different JA and GA pathways components, coupled with in vitro experiments to elucidate the crosstalk between these hormone pathways mediating SGAs metabolism. We discovered that reduced active JA results in decreased SGA production, while low levels of GA or its receptor led to elevated SGA accumulation. We showed that MYC1 and MYC2 transcription factors mediate the JA/GA crosstalk by transcriptional activation of SGA biosynthesis and GA catabolism genes. Furthermore, MYC1 and MYC2 transcriptionally regulate the GA signalling suppressor DELLA that by itself interferes in JA-mediated SGA control by modulating MYC activity through protein-protein interaction. Chemical and fungal pathogen treatments reinforced the concept of JA/GA crosstalk during SGA metabolism. These findings revealed the mechanism of JA/GA interplay in SGA biosynthesis to balance the cost of chemical defence with growth.
Keywords: alpha-tomatine; defence; gibberellin (GA); growth; jasmonate (JA); steroidal glycoalkaloids (SGAs); Tomato

BAHD-type acyltransferase concludes the biosynthetic pathway of non-bitter glycoalkaloids in ripe tomato fruit - Sonawane, Prashant D.; Gharat, Sachin A.; Jozwiak, Adam; Barbole, Ranjit; Heinicke, Sarah; Almekias-Siegl, Efrat; Meir, Sagit; Rogachev, Ilana; O'Connor, Sarah E.; Giri, Ashok P.; Aharoni, Asaph (Nature Communications, 2023)
During tomato fruit ripening, bitter and toxic steroidal glycoalkaloids (SGAs) are converted to nonbitter and less toxic forms, but proposed acylating enzyme in pathway remain unknown. Here, authors report BAHD-type acyltransferase that catalyze acylation step in biosynthesis of non-bitter SGAs in tomato. Tomato is the highest value fruit and vegetable crop worldwide, yet produces & alpha;-tomatine, a renowned toxic and bitter-tasting anti-nutritional steroidal glycoalkaloid (SGA) involved in plant defense. A suite of modifications during tomato fruit maturation and ripening converts & alpha;-tomatine to the non-bitter and less toxic Esculeoside A. This important metabolic shift prevents bitterness and toxicity in ripe tomato fruit. While the enzymes catalyzing glycosylation and hydroxylation reactions in the Esculeoside A pathway have been resolved, the proposed acetylating step remains, to date, elusive. Here, we discovered that GAME36 (GLYCOALKALOID METABOLISM36), a BAHD-type acyltransferase catalyzes SGA-acetylation in cultivated and wild tomatoes. This finding completes the elucidation of the core Esculeoside A biosynthetic pathway in ripe tomato, allowing reconstitution of Esculeoside A production in heterologous microbial and plant hosts. The involvement of GAME36 in bitter SGA detoxification pathway points to a key role in the evolution of sweet-tasting tomato as well as in the domestication and breeding of modern cultivated tomato fruit.

Parallel evolution of cannabinoid biosynthesis - Berman, Paula; de Haro, Luis Alejandro; Jozwiak, Adam; Panda, Sayantan; Pinkas, Zoe; Dong, Younghui; Cveticanin, Jelena; Barbole, Ranjit; Livne, Rotem; Scherf, Tali; Shimoni, Eyal; Levin-Zaidman, Smadar; et al. (Nature Plants, 2023)
This study reveals a cannabinoid biosynthetic pathway in Helichrysum umbraculigerum, a plant genetically distant from Cannabis, providing a potential source of new cannabinoids and metabolic engineering tools. Modulation of the endocannabinoid system is projected to have therapeutic potential in almost all human diseases. Accordingly, the high demand for novel cannabinoids stimulates the discovery of untapped sources and efficient manufacturing technologies. Here we explored Helichrysum umbraculigerum, an Asteraceae species unrelated to Cannabis sativa that produces Cannabis-type cannabinoids (for example, 4.3% cannabigerolic acid). In contrast to Cannabis, cannabinoids in H. umbraculigerum accumulate in leaves' glandular trichomes rather than in flowers. The integration of de novo whole-genome sequencing data with unambiguous chemical structure annotation, enzymatic assays and pathway reconstitution in Nicotiana benthamiana and in Saccharomyces cerevisiae has uncovered the molecular and chemical features of this plant. Apart from core biosynthetic enzymes, we reveal tailoring ones producing previously unknown cannabinoid metabolites. Orthology analyses demonstrate that cannabinoid synthesis evolved in parallel in H. umbraculigerum and Cannabis. Our discovery provides a currently unexploited source of cannabinoids and tools for engineering in heterologous hosts.

Steroidal scaffold decorations in Solanum alkaloid biosynthesis - Lucier, Rosalind; Kamileen, Mohamed O.; Nakamura, Yoko; Serediuk, Sofiia; Barbole, Ranjit; Wurlitzer, Jens; Kunert, Maritta; Heinicke, Sarah; O'Connor, Sarah E.; Sonawane, Prashant D. (Molecular Plant, 2024)
Steroidal glycoalkaloids (SGAs) are specialized metabolites produced by hundreds of Solanum species, including important vegetable crops such as tomato, potato, and eggplant. Although it has been known that SGAs play important roles in defense in plants and ``anti-nutritional''effects (e.g., toxicity and bitterness) to humans, many of these molecules have documented anti-cancer, anti-microbial, antiinflammatory, anti-viral, and anti-pyretic activities. Among these, a-solasonine and a-solamargine isolated from black nightshade (Solanum nigrum) are reported to have potent anti-tumor, anti-proliferative, and anti-inflammatory activities. Notably, a-solasonine and a-solamargine, along with the core steroidal aglycone solasodine, are the most widespread SGAs produced among the Solanum plants. However, it is still unknown how plants synthesize these bioactive steroidal molecules. Through comparative metabolomictranscriptome-guided approach, biosynthetic logic, combinatorial expression in Nicotiana benthamiana, and functional recombinant enzyme assays, here we report the discovery of 12 enzymes from S. nigrum that converts the starting cholesterol precursor to solasodine aglycone, and the downstream a-solasonine, a-solamargine, and malonyl-solamargine SGA products. We further identified six enzymes from cultivated eggplant that catalyze the production of a-solasonine, a-solamargine, and malonyl-solamargine SGAs from solasodine aglycone via glycosylation and atypical malonylation decorations. Our work provides the gene tool box and platform for engineering the production of high-value, steroidal bioactive molecules in heterologous hosts using synthetic biology.
Keywords: a-solamargine; Biosynthetic pathway; malonyl-solamargine; Solanum; Specialized metabolites; steroidal glycoalkaloids